AGAMA DAN KRISIS EKOLOGI: KETIDAKMAMPUAN PARA TOKOH DAN KIAI MELAWAN DOSA SEMEN DI REMBANG JAWA TENGAH - Roy Murtadho (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
The crimes against to the environment and the people of Indonesia, it is showed again in front of our eyes. The ruling of the Administrative Court judge of the Tribunal of State (PTUN) Semarang who rejected the lawsuit's overall Environment Forum (Walhi) and citizens of Rembang Central Java Governor against related permits the establishment of cement factories in Rembang on 16 April 2015, arguing the suit has expired, is not only a fallacy, more than that is their plotting evil politicians, legal and corporate to definitively destroy the island of Java. More so, the trial does not heed the fact that various Central Java Governor DECREE No. 660.1/17/2012 about the mining activities of the environmental permit for the cement factory in Indonesia Rembang, contrary to a number of laws. Mining in the North represent Kendeng Ciujung Group Portrait of a land conflict and deprivation of people's living space by large-scale extractive industries in Java. There are currently 77 mining permit material. The citizens of Java is mostly crowded and get the crisis of water, it should be avoided by mentaling. The agraria needs water which is not only dialy needs but also for the land of agraria. However, some of farmers is on the agrarian sector, which is done traditionally and subsistenly. If the mental industry is going to do more, the crisis of water and agrarian sector will be worse in Java.